1991
DOI: 10.1007/bf02026713
|View full text |Cite
|
Sign up to set email alerts
|

Familial neural crest tumours

Abstract: It is known that some cases of neural crest tumours are hereditary. We report the clinical and cytogenetic findings in a three-generation, extended family, four members of which developed single or multiple neural crest tumours (ganglioneuroma, ganglioneuroblastoma or neuroblastoma). To our knowledge, this is the first report of a family with three generations affected. No constitutional cytogenetic abnormality was found in the two members tested. We also review the literature on familial neural crest tumours,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Perhaps that sequence occurred in our patient, since metachronously and are most often reported in families with a history of neuroblastoma [12]. Our patient had none of the tumors were at an advanced stage when discovered.…”
mentioning
confidence: 54%
“…Perhaps that sequence occurred in our patient, since metachronously and are most often reported in families with a history of neuroblastoma [12]. Our patient had none of the tumors were at an advanced stage when discovered.…”
mentioning
confidence: 54%
“…Two individuals were shown to carry the PHOX2B mutation, samples from other affected individuals were not available. The full pedigree and clinical details are given in [Robertson et al, 1991]. the conservation of the amino acid through evolution, and the absence of the variant from controls strongly suggest that the mutation is pathogenic.…”
Section: Resultsmentioning
confidence: 98%
“…Tumor DNA was available from 35 cases. Clinical and linkage analyses in Family UB-NB3 have previously been reported [Robertson et al, 1991;Tonini et al, 2003;Longo et al, 2005].…”
Section: Subjectsmentioning
confidence: 96%
“…It has previously been reported that children with neuroblastoma have relatives with milder forms of the disease, i.e. benign ganglioneuromas (11, 12). Here we report on the markedly different histology in neuroblastic tumours arising in a mother and her two daughters.…”
Section: Discussionmentioning
confidence: 99%